Genetic risk factors for the posterior cortical atrophy variant of Alzheimer's disease. Issue 8 (16th March 2016) - Schott, Jonathan M.; Crutch, Sebastian J.; Carrasquillo, Minerva M.; Uphill, James; Shakespeare, Tim J.; Ryan, Natalie S.; Yong, Keir X.; Lehmann, Manja; Ertekin‐Taner, Nilufer; Graff‐Radford, Neill R.; Boeve, Bradley F.; Murray, Melissa E.; et al.
Abstract: Introduction: The genetics underlying posterior cortical atrophy (PCA), typically a rare variant of Alzheimer's disease (AD), remain uncertain. Methods: We genotyped 302 PCA patients from 11 centers, calculated risk at 24 loci for AD/DLB and performed an exploratory genome‐wide association study. Results: We confirm that variation in/near APOE/TOMM40 ( P = 6 × 10 −14 ) alters PCA risk, but with smaller effect than for typical AD (PCA: odds ratio [OR] = 2.03, typical AD: OR = 2.83, P = .0007). We found evidence for risk in/near CR1 ( P = 7 × 10 −4 ), ABCA7 ( P = .02) and BIN1 ( P = .04). ORs at variants near INPP5D and NME8 did not overlap between PCA and typical AD. Exploratory genome‐wide association studies confirmed APOE and identified three novel loci: rs76854344 near CNTNAP5 ( P = 8 × 10 −10 OR = 1.9 [1.5–2.3]); rs72907046 near FAM46A ( P = 1 × 10 −9 OR = 3.2 [2.1–4.9]); and rs2525776 near SEMA3C ( P = 1 × 10 −8, OR = 3.3 [2.1–5.1]). Discussion: We provide evidence for genetic risk factors specifically related to PCA. We identify three candidate loci that, if replicated, may provide insights into selective vulnerability and phenotypic diversity in AD.